Formulation and Evaluation of Lime Peel Extract (Citrus aurantiifolia) Gel with Semi-Refined Carrageenan and Glucomannan as Gelling Agent - Shervie Tjitrarukmana; Siti Malahayati; Liliana Swastina; Kunti Nastiti (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2022)
Lime peel extract contains quercetin with sunscreen activity. It could make into gel preparations, which has a transparent semisolid and generally gives a cooling sensation to the skin. A combination of semi-refined carrageenan and glucomannan as a gelling agent can be an alternative to form the strength and elasticity of the gel mass. This study aimed to determine the effect of concentration variations of gelling agents on the physical evaluation of gel preparation results and the optimal formulation for lime peel extract gel as sunscreen. Lime peel extract would make into gel preparation with variations in the concentration of the gelling agent, which are 1%, 1.25%, 1.5%, and 1.75%. Afterward, the physical evaluation included organoleptic, homogeneity, pH, viscosity, spreadability, and adhesion tests. The organoleptic, homogeneity, pH, and adhesion test results show that all formulations meet the requirements. Viscosity test results obtain the best formula III with 3940,00 cPs at 60 rpm . The results of the dispersibility test show the best formulas I and II with 6,10 cm and 5,50 cm. Based on the data analyzed, variations of gelling agents affect the pH, viscosity, spreadability, and adhesion test results. The optimal lime peel extract gel formulation has not defined from the physical evaluation results.